Interhemispheric balance of overt attention: a theta burst stimulation study. - Cazzoli, D; Wurtz, P; Müri, R; Hess, C; Nyffeler, T (2009)
Interhemispheric imbalance is discussed as a pathophysiological mechanism in visuospatial neglect. It is suggested that after a lesion of the right hemisphere the mutual transcallosal inhibition is impaired, resulting in an increased activity of the left hemisphere. We investigated the interhemispheric balance of attention in healthy subjects by using a free visual exploration task and by interfering with the neural activity of the posterior parietal cortex (PPC) of either hemisphere using an inhibitory transcranial magnetic stimulation routine with theta burst stimulation (TBS). Subjects explored colour photographs of real-life scenes presented on a computer screen under four conditions: (i) without TBS; (ii) after TBS over the right PPC; (iii) after TBS over the left PPC; and (iv) after TBS over the right PPC and, after the first half of the task, over the left PPC. Eye movements were measured, and distribution of mean cumulative fixation duration over screen halves was analyzed. TBS over the right PPC resulted in a significant rightward shift of mean cumulative fixation duration of approximately 30 min. The shift could be reversed when a subsequent train of TBS was applied over the left PPC. However, left PPC stimulation alone had no significant effect on visual exploration behaviour. The present study shows that the effect of TBS on the PPC depends on which hemisphere is stimulated and on the state of the contralateral homologue area. These findings are in accordance with the predictions of the interhemispheric rivalry model in neglect.